1993
DOI: 10.1007/bf00685339
|View full text |Cite
|
Sign up to set email alerts
|

Activity of continuous-infusion 5-fluorouracil in patients with advanced colorectal cancer clinically resistant to bolus 5-fluorouracil

Abstract: We have recently demonstrated that continuous-infusion (CI) 5-fluorouracil (FU) eradicates human colon carcinoma cells made resistant to bolus FU in vitro. In addition, in the same experimental system, the mechanisms of resistance to pulse and CI FU were found to be different. These observations led us to test the clinical activity of a standard regimen of CI FU (300 mg/m2 per day) in a cohort of 15 patients with advanced measurable colorectal cancer who were in progression after having failed to respond to bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…Low-dose, continuous infusion 5-FU produces a higher response rate than with other 5-FU regimens [3][4][5][6], but issues associated with continuous infusion remain.…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose, continuous infusion 5-FU produces a higher response rate than with other 5-FU regimens [3][4][5][6], but issues associated with continuous infusion remain.…”
Section: Introductionmentioning
confidence: 99%
“…The median time to progression for patients receiving second-line therapy is approximately 3 months and the median survival of these patients is 6-8 months. [12][13][14][15] A randomized phase III trial compared continuous infusion 5-FU to Irinotecan among patients who had failed prior treatment with a 5-FU regimen. 10 Only one partial response (PR) (0.7%) was observed among 134 patients treated with continuous infusion 5-FU and 6 (4.5%) PRs were observed in the irinotecan arm.…”
mentioning
confidence: 99%
“…17 The objective response rate for patients in this study was 8% and the median survival was 11 months, exceeding the expected response rate of 2-5% and survival of 4-6 months for patients with refractory colorectal cancer. [18][19][20][21][22] Although the objective response rate was encouraging, standard radiographic response criteria may not have captured important clinical responses with this biologically active agent. 12,17,23 Forty-six percent of the patients in the phase II study demonstrated transient enlargement of the tumor masses 3 weeks after administration of Onyx-015 followed by regression of the tumors starting 2-3 months after initiation of therapy.…”
Section: Introductionmentioning
confidence: 99%